2023
DOI: 10.1021/acsami.3c03528
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan-Mediated Oral Codelivery of 5FU and Bcl2 siRNA Attenuates Stomach Cancer

Humayra Afrin,
Stephanie Vargas Esquivel,
Raj Kumar
et al.

Abstract: Based on cancer-related deaths, stomach cancer is ranked fifth, and first among Hispanics. Lack of technologies for early diagnosis and unavailability of targetspecific therapeutics are largely the causes of the poor therapeutic outcomes from existing chemotherapeutics. Currently available therapeutic modalities are invasive and require systemic delivery, although the cancer is localized in the stomach at its early stage. Therefore, we hypothesize that an oral local delivery approach can extend the retention d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…For instance, we have reported an omega-3 fatty acid cross-linked ionic liquid that has shown mucoadhesive properties and maintained its retention within the intestine for more than 6 h upon oral administration . Along the same line, we have reported development of a polysaccharide-based mucoadhesive oral vehicle that also maintained its intestinal retention for 6–8 h upon oral administration. , We have tested their feasibilities for synthetic small molecules as well nucleic acid oral delivery in a small animal model. These vehicles hold strong promise for oral immunomodulator delivery to improve the mucosal immunity.…”
Section: Different Formulations For Enhancing Mucosal Immunitymentioning
confidence: 85%
“…For instance, we have reported an omega-3 fatty acid cross-linked ionic liquid that has shown mucoadhesive properties and maintained its retention within the intestine for more than 6 h upon oral administration . Along the same line, we have reported development of a polysaccharide-based mucoadhesive oral vehicle that also maintained its intestinal retention for 6–8 h upon oral administration. , We have tested their feasibilities for synthetic small molecules as well nucleic acid oral delivery in a small animal model. These vehicles hold strong promise for oral immunomodulator delivery to improve the mucosal immunity.…”
Section: Different Formulations For Enhancing Mucosal Immunitymentioning
confidence: 85%
“…Changes in modern diet culture and lifestyle have led to an increase in the prevalence of gastrointestinal-related diseases, particularly long-term or severe digestive system diseases that could increase the risk of gastric cancer. Studies have demonstrated a significant association between consuming processed foods rich in salt, pickled foods, and processed meat and an increased risk of gastric cancer, which is particularly prevalent in Asian countries . Furthermore, some Asians face increased exposure to plasticizers, such as phthalates and bisphenols, compared to other populations, primarily due to the widespread utilization of plastic products. , Di­(2-ethylhexyl) phthalate (DEHP), the predominant plasticizer used to make polyvinyl chloride (PVC) products flexible, such as medical devices and pharmaceuticals, contributes up to 40% of the weight of intravenous bags and is present in more than 80% of the weight of medical tubing. , DEHP is also used to manufacture flexible plastics for various applications, such as food packaging, indoor decorations, and children’s toys.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in modern diet culture and lifestyle have led to an increase in the prevalence of gastrointestinal-related diseases, particularly long-term or severe digestive system diseases that could increase the risk of gastric cancer. 1 3 Studies have demonstrated a significant association between consuming processed foods rich in salt, pickled foods, and processed meat and an increased risk of gastric cancer, which is particularly prevalent in Asian countries. 4 Furthermore, some Asians face increased exposure to plasticizers, such as phthalates and bisphenols, compared to other populations, primarily due to the widespread utilization of plastic products.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, relevant studies have confirmed that ( 12 ), as an immune modulator, β-glucan has shown positive effects in inhibiting tumor cell proliferation and activating anti-tumor immune responses ( 13 16 ). Meanwhile, due to its stable structure, it is also used as a component of oral anti-tumor drug delivery carriers ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…β-Glucan, a powerful immunomodulator, has exhibited remarkable anti-tumor efficacy in preclinical investigations targeting colorectal, pancreatic, and gastric cancers ( 14 , 24 , 25 ). Notably, its high stability underscores its significance as a carrier for targeted drugs specifically designed to combat gastric cancer ( 17 ). Clinical studies further validate its ability to enhance the 5-year survival rate in patients with hepatocellular carcinoma, gastric cancer, and colorectal cancer, while simultaneously reducing the rate of recurrence ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%